Grb14 mRNA Levels During Follicular Deviation in Cattle are Higher in Granulosa Cells of Subordinate Compared to Dominant Follicles. Issue 3 (1st October 2012) - Bohrer, RC; Rosa, PRA; Ferreira, R; Bordignon, V; Oliveira, JFC; Gonçalves, PBD
Contents: The growth factor receptor‐bound protein 14 (Grb14) is a cellular adapter protein belonging to the Grb7 family of proteins. Studies with human and rodent cells have demonstrated that Grb14 acts as a negative regulator of tyrosine kinase receptor signalling through the MAPK and PI3K pathways. In cattle, tyrosine kinase receptors are activated during follicular development but the role of Grb14 in this process has not yet been investigated. Therefore, the aim of the present study was to characterize Grb14 mRNA expression in ovarian somatic cells during follicular growth and deviation in cattle. We found Grb14 mRNA expressed in both granulosa and theca cells derived from follicles at different stages of development (3–5 , 6–8, >8 mm in diameter). The abundance of mRNA for Grb14 was higher in granulosa cells of subordinate compared with those from dominant follicles at days 3 and 4 of the follicular wave (p < 0.05). Further, there was a negative correlation between the abundance of mRNA for Grb14 and P450Arom in granulosa cells ( R 2  = 0.367; p < 0.05) and between the abundance of mRNA for Grb14 in granulosa cells and concentration of oestradiol in follicular fluid ( R 2  = 0.545; p < 0.05). In theca cells, the expression of Grb14 mRNA did not differ between dominant and subordinate follicles (p > 0.05). These findings suggest that Grb14 may play a regulatory role in granulosa cells during follicular deviation in cattle.